Conservation of ’Pedro Sato’ guavas under treatment with 1-methylcyclopropene - Bassetto, Eliane; Jacomino, Angelo Pedro; Pinheiro, Ana Luiza (Pesquisa Agropecuaria Brasileira, 2005)
The search for techniques that extend shelf life of guava (Psidium guajava) fruits, and reduce its postharvest losses is desirable. The objective of this work was to evaluate the effects of concentrations of competitive ethylene antagonist 1-methylcyclopropene (1-MCP) on conservation of ’Pedro Sato’ guava fruits. Treatments consisted of 0, 100, 300 or 900 nL L-1 of 1-MCP for 3 hours followed by storage at 25ºC, and 10ºC with 90±5% RH. The application of 900 nL L-1 1-MCP for 3 hours was efficient in delaying loss of skin color, and in keeping fruit firmness at both storage temperatures. The 300 nL L-1 of 1-MCP concentration was efficient in delaying skin color loss only when fruits were stored at 10ºC. The effect of 1-MCP was quite significant on the reduction of rot incidence at both storage temperatures. The respiratory rate was lower in fruits treated with 300 and 900 nL L-1 of 1-MCP during storage at 25ºC. The product was efficient in delaying the ripening of fruits, and the concentration of 900 nL L-1 showed the best effect.